The punch : a novel - Hawley, Noah (Chronicle Books, 2008)
Joe Henry was the glue that held his family together. Now he is dead, and his wife and sons are coming together for one final journey to scatter his ashes. First, however, his loved ones have some things to work out. David, the older son, believes that any minute his life is going to fall apart and everyone he loves will leave him. His brother Scott can't shake the belief that at heart, people are inherently rotten. Doris, their mother, just doesn't believe in anything anymore. Wickedly funny and biting, THE PUNCH is an essential exploration of modern American grief, family violence, and redemption from the bestselling author of BEFORE THE FALL and creator of the Emmy award-winning series FARGO.